Cash Assistance: Addressing COVID-19 Pandemic-induced Poverty: Bantuan Sosial Tunai: Solusi Atasi Kemiskinan Pandemi COVID-19 - Khisbi, Mochammad Alfalah; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2023)
This study employs Edward III's policy implementation theory to examine the implementation of the Social Cash Assistance (BST) program in Gebang Village, Sidoarjo Regency. Utilizing a descriptive qualitative method with data gathered through observation, interviews, and documentation, the research identifies communication, resources, dispositions, and bureaucratic structure as critical factors. The findings reveal that the BST program in Gebang Village has been effectively executed, with robust communication facilitated through coordination meetings and outreach. Human resources, comprising village employees and supporting staff, demonstrate high commitment and operate within health protocol guidelines. Despite optimal implementation, challenges such as limited beneficiaries, social jealousy, and program discontinuation in 2022 are identified. The study underscores the need for addressing these challenges to enhance the program's sustainability and effectiveness. Highlight : The study employs Edward III's policy implementation theory to analyze the optimal execution of the Social Cash Assistance (BST) program in Gebang Village, Sidoarjo Regency. Effective communication strategies, including coordination meetings and program outreach, contribute to the successful implementation of the BST program, ensuring high commitment from the village employees and supporting staff. Identified challenges, such as limited beneficiaries, social jealousy, and the discontinuation of the BST program in 2022, underscore the importance of addressing obstacles for enhanced program sustainability and effectiveness. Keywords: Social Cash Assistance, Implementation, Gebang Village, Policy, Challenges